Knowledge, attitude and practice of women aged 15 and above on breast cancer: a case study of lalitpur sub municipality, ward no 4. - Dhakal, Archana (2008)
SUMMARY: Every woman in this world is at risk of breast cancer. This disease is a rising problem in Nepal. More and more people are found to have breast cancer. This cancer happens primarily to women. The tragedy is that, in most of the cases, the cancer is found in its latter stage. If the cancer were found in its earlier stages; not only time, stress and money could have been minified, but also precious life of the sick would be saved. To combat this disease, awareness of people is the answer because early recognition of cancer gives the best chance of getting rid of the disease. In this survey, it was found that 91% of the respondents had heard about breast cancer from which 82% had heard from media (i.e. TV and radio). With regard to risk factors of breast cancer, 11% of the respondents gave 0% correct answer, 42% of the respondents gave less than 30% correct answer, 30% of the respondents gave about 30%-50% correct answer, 11% of the respondents gave 50%-70% correct answer, 7% of the respondents gave 70%-100% correct answer and, 0% of the respondents gave 100% correct answer. With regard to methods of early detection of breast cancer; only 9% gave correct answer, 35% of the respondents said they don't know and the other 56% had incomplete knowledge about it. 70% of respondents think that this disease is preventable, 21% think it as a curse and 16% think it as incurable disease. 88% of respondents said they had never ever performed BSE. With regard to finding abnormality in their breast: 74% said they would go to modern health care provider. School health books should include breast cancer in the syllabus so that the coming generation become aware and sincere and subsidies or low price should be given to checkup and treatment of breast cancer. The INGOs and NGOs should conduct their awareness program with more rigor and frequency so that all the participants are crystal clear about all aspects of the cancer. Articles, programs on breast cancer should be made a priority by all kinds of media.